On the evolution of process-oriented approaches for healthcare workflows. (1st January 2013) - Russo, Alessandro; Mecella, Massimo
In the healthcare domain, a wide range of processes with different characteristics and requirements are executed, ranging from highly standardised procedures to less structured ones that reflect the knowledge-intensive nature of clinical decision making. Healthcare is thus widely recognised as one of the most promising, yet challenging, domains for the adoption of process-oriented models and solutions able to support organisational and clinical processes. In this paper, we provide an up-to-date overview that presents and discusses the application of process-oriented solutions in the healthcare domain. Our analysis covers both administrative/organisational processes and medical processes, and we consider contributions and research efforts produced by the business process management (BPM) community and the medical informatics community. We delineate the overall evolution that has been observed from imperative and activity-centric approaches to the emergence of declarative data-centric methodologies, including the recent trends towards adaptive case management in healthcare.